P558 A retrospective study of management of Henoch Schonlein (HSP) nephritis in children in Ireland A. (June 2019) - Stephens, Carol; Conlon, Tracy; Waldron, Mary; Stack, Maria
Abstract : HSP is a prevalent disease with an incidence of 6–24 per 100, 000.(1) It can lead to significant chronic disease with renal involvement being the principal cause. It requires close monitoring and treatment. Renal biopsies can be important prognostic markers and guide best management.(2) Currently, there have been no significant randomised controlled trials detailing best management and hence treatment varies significantly. This study reviews practice in a national tertiary renal unit in Ireland over a fifteen-year period. Aims: 1. Identify children who had a renal biopsy. 2. Review Medical management, duration of therapy and follow up. Methods: This was a retrospective review between September 2001 to April 2017. Data was collated by computer and paper records, online haematological and radiological resources. This review excludes children managed in another tertiary centre in Ireland. Results: The main outcomes were: patient demographics, (i) Biopsy findings: Acute vs Chronic and staging classification, (ii) Drug Treatment and Duration (iii) Follow up: urinanalysis at interval time points, renal ultrasonography and renal function. Thirty children had a renal biopsy. 10 For persistent proteinuria, 2 for recurrent episodes, deranged renal function, mixed nephritic/nephrotic, IgA vs HSP respectively and 12 not classified. 73% required medical treatment, the majority polypharmacy. When immunosuppressants were needed a combination of steroids and Mycophenolate Acid were most commonly used. 73% required medical treatment for over eighteen months with evidence of proteinuria often guiding duration. Regular follow up included urinanalyis, renal bloods, ultrasonography and blood pressure measurement. To standarise care nationally, a basic guideline was created to aid appropriate referral to our tertiary centre. Conclusion: HSP is rare but can cause significant morbidity. RCTs are required to determine best management and to standardize care nationally and internationally